2017
DOI: 10.4197/med.24-2.6
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to Insulin Analogs in Gestational Diabetes

Abstract: Since human recombinant insulin preparations has been introduced in medicine, allergies to insulin have rarely been reported, especially in pregnant women, who experience immune system alterations that are due to physiologic changes that occur during pregnancy. We describe a 41-year old woman who developed gestational diabetes during the second trimester and was initially treated with insulin aspart and detemir. She complained of itching, redness and a burning sensation at insulin injection sites a few weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A study in India concluded that women with GDM and hypothyroidism require intense surveillance and screening for other comorbidities, as they face an increased risk of perinatal complications [2]. In addition, several studies worldwide have shown that overt, subclinical hypothyroidism and anti-thyroid peroxidase (anti-TPO) are more prevalent among the pre-GDM group [10] and GDM group [11][12][13][14]. These findings indicate that routine screening is necessary for all patients with DM or an increased risk of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…A study in India concluded that women with GDM and hypothyroidism require intense surveillance and screening for other comorbidities, as they face an increased risk of perinatal complications [2]. In addition, several studies worldwide have shown that overt, subclinical hypothyroidism and anti-thyroid peroxidase (anti-TPO) are more prevalent among the pre-GDM group [10] and GDM group [11][12][13][14]. These findings indicate that routine screening is necessary for all patients with DM or an increased risk of GDM.…”
Section: Introductionmentioning
confidence: 99%